Non-Ulcerated and Ulcerated Necrotizing Sialometaplasia: Report of an Additional Case and Literature Review - Silva, Evânio Vilela [UNESP]; Silveira, Heitor Albergoni [UNESP]; Moreira, Thales Peres Candido; Augusto, Jefferson; Silva, Paula Verona Ragusa [UNESP]; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Springer Nature, 2023)
Necrotizing sialometaplasia (NS) is a rare, self-limiting, necrotizing inflammatory lesion, often involving the minor salivary glands of the palate. NS occurs often in men (60%) older than 45 years. Commonly, it presents as an ulcerative lesion, measuring 1 to 3 cm in diameter, with an evolution time of a few weeks or days, simulating malignancy. However, in some instances, the mucosal surface is intact, thus emphasizing the importance of considering NS in the differential diagnosis of oral ulcerative and non-ulcerative lesions. To date, 12 cases of non-ulcerated NS in the palate have been reported. Here, we report a 50-year-old male patient who presented a non-ulcerated, asymptomatic, nodular swelling 3 months ago, located on the hard palate, clinically suggesting salivary gland tumor or lymphoproliferative disorder. After biopsy, a diagnosis of non-ulcerated NS was established. After 4 weeks, the lesion evolved with complete resolution. After literature review, notably, unlike ulcerated NS, the non-ulcerated NS affected patients a decade younger (33 years vs. 45 years), with marked female predilection (83% vs. 40%) and not uncommon bilateral presentation (33% vs. 10%). NS should be considered in the differential diagnosis of ulcerative and non-ulcerative lesions affecting the palate.
Keywords: Immunohistochemistry; Necrotizing sialometaplasia; Oral mucosa; Palate; Salivary gland diseases